2017
DOI: 10.1111/age.12537
|View full text |Cite
|
Sign up to set email alerts
|

On the origins and genetic diversity of South American chickens: one step closer

Abstract: Local chicken populations are a major source of food in the rural areas of South America. However, very little is known about their genetic composition and diversity. Here, we analyzed five populations from South America to investigate their maternal genetic origin and diversity, hoping to mitigate the lack of information on local chicken populations from this region. We also included three populations of chicken from the Iberian Peninsula and one from Easter Island, which are potential sources of the first ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
1
9
0
3
Order By: Relevance
“…The results from the D-loop inference demonstrate that the Ecuadorian chicken originated from at least two different sources. Both linages were identifiable with the European strain and with the Asian type, demonstrating the presence of pre-Columbian influence on the actual population, as was also recently demonstrated in other South American populations, including the Ecuadorian chicken, by other authors [47]. The complete history of the chicken in South America will require the extension of this kind of study to more populations, because the introduction of animals even from the Pacific Ocean could have occurred at different moments and from different starting populations, so our knowledge about mitochondrial DNA diffusion is likely to be changed in the future.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results from the D-loop inference demonstrate that the Ecuadorian chicken originated from at least two different sources. Both linages were identifiable with the European strain and with the Asian type, demonstrating the presence of pre-Columbian influence on the actual population, as was also recently demonstrated in other South American populations, including the Ecuadorian chicken, by other authors [47]. The complete history of the chicken in South America will require the extension of this kind of study to more populations, because the introduction of animals even from the Pacific Ocean could have occurred at different moments and from different starting populations, so our knowledge about mitochondrial DNA diffusion is likely to be changed in the future.…”
Section: Discussionsupporting
confidence: 79%
“…Haplogroup E has been observed in the Chilean Araucana chicken [3], which reflects the persistence of ancient Polynesian haplogroups [47]. In the present study, as was previously reported in the Chilean chicken [4], haplotypes belonging to the geographically broad type E were found; this haplogroup has been identified in European animals (Plymouth Rock, White Plymouth Rock, White Leghorn, and New Hampshire), as well as in the Middle East, India, and China [45].…”
Section: Discussionmentioning
confidence: 99%
“…Several questions could arise from this last result, mainly regarding why South America, having a strong economic nexus with the US, seems to be the last geographic area colonized by MG. Notoriously, before 1950, the local poultry was sustained by backyard producers that used local breeds such the Araucana chicken, among others [ 70 ], instead of imported breeds. It is important to highlight that the South American chickens had good economic indicators and were well adapted to the region since their introduction seems to be pre-Columbian [ 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to highlight that the South American chickens had good economic indicators and were well adapted to the region since their introduction seems to be pre-Columbian [ 71 ]. With the advent of the modern poultry industry, several commercial flocks were installed in South America using the cosmopolitan commercial lineages [ 70 ], this being the most probable cause of introduction of MG into the region. Analyzing the support for the routes of transmission of MG using Bayes factor (BF) BF > 5 ( Figure 2 B), a high level of connection among different countries was revealed, evidencing the high degree of spreading of MG and its pandemic characteristic.…”
Section: Resultsmentioning
confidence: 99%
“…The 21 chicken lines belonged to one of the three D-loop haplogroups (A, D, and E) out of the eight common haplogroups (A–H) that had been previously defined using data from 347 commercial chickens, 4,385 indigenous chickens from around the world, and 206 red junglefowls [39]. Among the eight common haplogroups, haplogroup E was the most predominant, followed by haplogroup A. Haplogroup E is considered to have originated from the Indian subcontinent and is contemporary prevailed in the global chicken populations [6, 26, 33, 34, 36, 37, 45]. Haplogroup A may be of Chinese origin and includes indigenous chickens from China, Japan, and South and Southeast Asia [1, 26, 33].…”
Section: Discussionmentioning
confidence: 99%